2013
DOI: 10.2217/iim.13.46
|View full text |Cite
|
Sign up to set email alerts
|

Advancing our understanding of the brain in autism: contribution of functional MRI and diffusion tensor imaging

Abstract: Advancing our understanding of the brain in autism: contribution of functional MRI and diffusion tensor imaging Neuroimaging research in the last two decades has contributed significantly in illuminating our knowledge of the neurobiology of autism spectrum disorders. Using modern brain imaging methods, particularly functional MRI and diffusion tensor imaging, researchers have examined the make-up and functioning of the brain in autism. Findings of widespread functional, anatomical and connectional abnormalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 120 publications
0
5
0
Order By: Relevance
“…Autism spectrum disorder (ASD) has been characterized as a disorder of neurodevelopmental origin, with widespread abnormalities such as altered cortical anatomy (Amaral, Schumann, & Nordahl, 2008; Nickl-Jockschat et al, 2012), abnormal white matter (WM) integrity (Travers et al, 2012), altered brain function and connectivity (Anagnostou & Taylor, 2011; Kana, Libero, & Moore, 2011; Libero & Kana, 2013; Maximo, Cadena, & Kana, 2014; Schipul, Keller, & Just, 2011), increase in the number of neurons (Courchesne, Campbell, & Solso, 2011), numerous and smaller cortical minicolumns (Casanova, Buxhoeveden, & Brown, 2002; Casanova, Buxhoeveden, Switala, & Roy, 2002; Casanova et al, 2006), and alterations in synaptic connections and the organization of neurons within cortex (Avino & Hutsler, 2010; Hutsler, Love, & Zhang, 2007; Hutsler & Zhang, 2010; Stoner et al, 2014). Such abnormalities point to a complex and multilayered picture of the neurobiology of autism.…”
Section: Introductionmentioning
confidence: 99%
“…Autism spectrum disorder (ASD) has been characterized as a disorder of neurodevelopmental origin, with widespread abnormalities such as altered cortical anatomy (Amaral, Schumann, & Nordahl, 2008; Nickl-Jockschat et al, 2012), abnormal white matter (WM) integrity (Travers et al, 2012), altered brain function and connectivity (Anagnostou & Taylor, 2011; Kana, Libero, & Moore, 2011; Libero & Kana, 2013; Maximo, Cadena, & Kana, 2014; Schipul, Keller, & Just, 2011), increase in the number of neurons (Courchesne, Campbell, & Solso, 2011), numerous and smaller cortical minicolumns (Casanova, Buxhoeveden, & Brown, 2002; Casanova, Buxhoeveden, Switala, & Roy, 2002; Casanova et al, 2006), and alterations in synaptic connections and the organization of neurons within cortex (Avino & Hutsler, 2010; Hutsler, Love, & Zhang, 2007; Hutsler & Zhang, 2010; Stoner et al, 2014). Such abnormalities point to a complex and multilayered picture of the neurobiology of autism.…”
Section: Introductionmentioning
confidence: 99%
“…The Complex Information Processing model has received further support from the results of neurofunctional investigations, using functional magnetic resonance imaging (fMRI; see reviews Just et al, 2012; Libero and Kana, 2013). An initial fMRI study of sentence comprehension, with older adolescents and young adults with autism and age- and ability-matched controls, indicated that, in general, the brains of the individuals with autism were organized in the same way as that of the controls with typical development; however, areas of the brain were not working together to optimally support language function (Just et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This is highlighted by a systematic review by Libero and Kana (2013) of a number of neuroimaging studies, which correlated brain measures with behavioral or diagnostic instruments in order to further understand the relationship between biology and behavior and to better understand the origins of ASD symptoms and the varying levels of severity. This is highlighted by a systematic review by Libero and Kana (2013) of a number of neuroimaging studies, which correlated brain measures with behavioral or diagnostic instruments in order to further understand the relationship between biology and behavior and to better understand the origins of ASD symptoms and the varying levels of severity.…”
Section: Discussionmentioning
confidence: 99%